2022
DOI: 10.3390/antiox11020221
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside and Quercitrin in Houttuynia cordata Extract Attenuate UVB-Induced Human Keratinocyte Cell Damage and Oxidative Stress via Modulation of MAPKs and Akt Signaling Pathway

Abstract: Ultraviolet radiation is a major environmental harmful factor on human skin. In this paper, we investigate the potential mechanism of Houttuynia cordata extract on UVB-induced HaCaT keratinocyte cell death and inflammation. We found that Houttuynia cordata ethyl acetate extract fraction (HC-EA) protected against UVB-induced cell damage. The HPLC results indicate that quercitrin and hyperoside are the major polyphenolics in HC-EA and are responsible for providing protection against UVB-induced cell death. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 59 publications
2
6
0
1
Order By: Relevance
“…Thus, we suggest that the activation of Nrf2 by limonene is a JNK/SAPK‐ and AKT‐dependent mechanism. A previous study also suggested that exposure of HaCaT cells to dietary phytochemicals, such as hyperoside and quercitrin promote Nrf2 accompanied by the activation of JNK/SAPK and AKT 35 . Based on our results, limonene promoted Nrf2 activation and induction of antioxidant regulators, which were critical protective molecules for the skin against UVB‐induced photodamage.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, we suggest that the activation of Nrf2 by limonene is a JNK/SAPK‐ and AKT‐dependent mechanism. A previous study also suggested that exposure of HaCaT cells to dietary phytochemicals, such as hyperoside and quercitrin promote Nrf2 accompanied by the activation of JNK/SAPK and AKT 35 . Based on our results, limonene promoted Nrf2 activation and induction of antioxidant regulators, which were critical protective molecules for the skin against UVB‐induced photodamage.…”
Section: Discussionsupporting
confidence: 81%
“…Myricetin was also reported to regulate Akt signaling for improving skeletal muscle function in fructose-fed rats [ 36 ]. Hyperoside was found to affect Akt signaling for exerting effects in vivo and in vitro [ 37 , 38 ]. The positive effect of BBE on the Akt-FoxO1 pathway may be attributed to the presences of myricitrin, myricetin, and hyperoside.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet B rays produce electromagnetic energy. 32 Epidermal cells are modulated by UV electromagnetic waves, and although each one has a function, they share a communication network. 10 , 13 This modulates cutaneous sensory transduction, 33 influencing both inflammatory responses and the immune and endocrine systems as a whole.…”
Section: Introductionmentioning
confidence: 99%